A political history of the subjectivity in Michel Foucault (Fractal: Journal of Psychology, 2009)
This investigated corresponds to the question of the subjectivity in Foucault from a critical reading. In archaeology it is evidenced existence of the subject of the enunciation while it appears derived from the objectivization games. In the genealogy, the notion appears of situated individual in the relations of power. In the genealogy of the ethics, the subject produced for the ethical experiences. Concludes that against the universalism of  the subject’s theories, these forms of subjectivity point with respect to a “historical ontologies of ourselves” letting not to discover what we are, and yes to refuse what in we become them.